2021
DOI: 10.1037/fsh0000581
|View full text |Cite
|
Sign up to set email alerts
|

Mental health therapists’ perceived barriers to addressing intimate partner violence and suicide.

Abstract: Introduction: Intimate partner violence (IPV) and suicide are pressing public health issues, yet their intersection in mental health care settings is understudied. We conducted a qualitative study to characterize mental health therapists' personal and system barriers in preparation for an upcoming training curriculum seeking to help patients address these interconnected issues. Method: We partnered with an urban community mental health center in New York to facilitate focus groups grounded in communitybased pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The WHO found that IPV affects approximately 641 million women globally, making it the most prevalent form of violence against women (WHO, 2021). IPV has a range of effects on the victimized partner, including but not limited to physical injury, suicidality, depression, anxiety, substance use, posttraumatic stress disorder (PTSD), selfharm, sexually transmitted diseases, and injury to reproductive health (Beck et al, 2016;Kubany & Watson, 2002;Lahav, Renshaw, & Solomon, 2019;Lahav et al, 2018;Willie et al, 2018;Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO found that IPV affects approximately 641 million women globally, making it the most prevalent form of violence against women (WHO, 2021). IPV has a range of effects on the victimized partner, including but not limited to physical injury, suicidality, depression, anxiety, substance use, posttraumatic stress disorder (PTSD), selfharm, sexually transmitted diseases, and injury to reproductive health (Beck et al, 2016;Kubany & Watson, 2002;Lahav, Renshaw, & Solomon, 2019;Lahav et al, 2018;Willie et al, 2018;Wilson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The referral centres should be all inclusive centres that can provide holistic care to women who have experienced IPV. Miller et al [ 13 ], and Wilson et al [ 10 ], confirmed that lack of referral centres makes it futile to screen for IPV. They advised that referral centres facilitate pregnant women's access to social services, support, and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, barriers to routine screening have been reported in many midwifery settings globally. These include lack of time due to huge workload, lack of privacy due to the presence of pregnant women's partners, lack of resources, and absence of implementable policies, protocols and guidelines [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…While several disciplines including gynecology, pediatrics, psychology, and emergency medicine have been encouraged by national organizations to screen for IPV, professionals across these disciplines also routinely report barriers to screening. Healthcare professionals note hesitations based on (a) a lack of training and confidence in asking about IPV sensitively, (b) fear of causing offense, (c) feeling ill‐equipped to follow‐up with a positive screen, and (d) insufficient time to screen (Aregger Lundh et al, 2023; Schilling et al, 2012; Thackeray et al, 2010; Wilson et al, 2021). While many proposals have attempted to address these barriers by increasing system wide training and harnessing technology to assist with screening (Mancheno et al, 2020; Schilling et al, 2012), these changes are slow and screening for IPV remains significantly less frequent than screening for other psychosocial factors like depression or anxiety (Perone et al, 2022).…”
Section: Challenges In Assessment and Referral For Treatmentmentioning
confidence: 99%